2016
DOI: 10.4103/1735-3327.192269
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion among Iranian children: A systematic review and meta-analysis

Abstract: Background:The high prevalence of malocclusion is a public health problem in the world and the third priority in oral care. Numerous primary studies have presented reports on the prevalence of malocclusion among Iranian children. In combination, the results of these studies using meta-analysis are highly valuable for health policy-making. Similarly, this study aimed at determining the prevalence of different types of malocclusion among Iranian children.Materials and Methods:Using relevant keywords, national an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…These results are both similar to those revealed by other studies conducted in Central and South Romania and unlike the results of a research on the Iranian child population, where the prevalence of Angle Class I and III malocclusions was 1.09 and 1.23 times higher, respectively, in girls than in boys. A study on the orthodontic treatment needed by Colombian children conducted by Thilander et al also reported a higher prevalence of Class III malocclusion in girls than in boys [13,35,39,49].…”
Section: Discussionmentioning
confidence: 99%
“…These results are both similar to those revealed by other studies conducted in Central and South Romania and unlike the results of a research on the Iranian child population, where the prevalence of Angle Class I and III malocclusions was 1.09 and 1.23 times higher, respectively, in girls than in boys. A study on the orthodontic treatment needed by Colombian children conducted by Thilander et al also reported a higher prevalence of Class III malocclusion in girls than in boys [13,35,39,49].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 It is one of the most common dental problems, with high prevalence ranging from 20% to 100% reported by different researchers. 3 5 Disparity in the recorded data may ascribe to the difference in geographic position, age of included groups, registration procedures, and others. Deep overbite, midline deviation, excessive overjet, anterior crossbite, mal-alignment, space, and open bite are frequently seen types of malocclusion in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Data from epidemiological studies investigating the prevalence and severity of malocclusions in children are of great relevance to the implementation of public health programs aimed at orthodontic prevention. In this context epidemiology becomes a useful tool for the early diagnosis of malocclusions, contributing to the limitation of further aggravations of the same during the later stages of growth ( 1 - 4 ).…”
Section: Introductionmentioning
confidence: 99%